Columnar specificity of intrinsic horizontal and corticocortical connections in cat visual cortex - Gilbert, CD (J Neurosci, 1989)
A prominent and stereotypical feature of cortical circuitry in the striate cortex is a plexus of long-range horizontal connections, running for 6–8 mm parallel to the cortical surface, which has a clustered distribution. This is seen for both intrinsic cortical connections within a particular cortical area and the convergent and divergent connections running between area 17 and other cortical areas. To determine if these connections are related to the columnar functional architecture of cortex, we combined labeling of the horizontal connections by retrograde transport of rhodamine-filled latex microspheres (beads) and labeling of the orientation columns by 2- deoxyglucose autoradiography. We first mapped the distribution of orientation columns in a small region of area 17 or 18, then made a small injection of beads into the center of an orientation column of defined specificity, and after allowing for retrograde transport, labeled vertical orientation columns with the 2-deoxyglucose technique. The retrogradely labeled cells were confined to regions of orientation specificity similar to that of the injection site, indicating that the horizontal connections run between columns of similar orientation specificity. This relationship was demonstrated for both the intrinsic horizontal and corticocortical connections. The extent of the horizontal connections, which allows single cells to integrate information over larger parts of the visual field than that covered by their receptive fields, and the functional specificity of the connections, suggests possible roles for these connections in visual processing.